Paclitaxel-Induced Hepatotoxicity in Ovarian Cancer Patients: A Case Report - Haoran Yang PharmD; Lina Shen MD; Yunzhi Yang BS; Xiaoyu Li PhD (SAGE Publishing, 2024)
Paclitaxel plus carboplatin is the most common regimen for the treatment of ovarian cancer. While generally effective, these chemotherapy agents can cause adverse events such as myelotoxicity, nausea, vomiting, and rarely, hepatotoxicity. Paclitaxel is associated with mild elevations in serum aminotransferase levels, but significant hepatotoxicity is uncommon, particularly in patients without prior liver disease. We present a patient with ovarian cancer who developed significant elevation of serum aminotransferases up to 12 times the upper limit of normal after the first cycle of paclitaxel plus carboplatin chemotherapy. Extensive evaluations excluded other potential causes of liver injury and the diagnosis of paclitaxel-induced liver injury was confirmed. The patient was treated with liver protective medications and a reduced dose of paclitaxel (135 mg/m 2 ) for subsequent cycles. Her liver function tests stabilized within 2 to 3 times the upper limit of normal, allowing continuation of chemotherapy and achieving a favorable outcome.